2021
DOI: 10.1093/braincomms/fcab258
|View full text |Cite
|
Sign up to set email alerts
|

Reading cognition from the eyes—association of retinal nerve fiber layer thickness with cognitive performance in a population-based study

Abstract: With the eye as window to the brain, non-invasive fast screening of retinal nerve fiber layer thickness poses the opportunity for early detection of cognitive decline leading to dementia. Our objective is to determine whether performance in various neurocognitive tests has an association with itemized retinal nerve fiber layer thickness. Detailed investigation of associations factored in sex and eye-side. The large population-based LIFE-Adult study (Leipzig Research Centre for Civ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…In our present study, we showed retinal thicknesses and retinal microvasculature had a significant correlation with Stroop parameters which is in line with previous reports ( van Koolwijk et al, 2009 ; Mutlu et al, 2018 ). Our findings suggest that GCIPL thickness and SVC density may reflect cognitive dysfunction which is in line with previous reports ( Jones-Odeh et al, 2016 ; Ko et al, 2018 ; Girbardt et al, 2021 ; Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our present study, we showed retinal thicknesses and retinal microvasculature had a significant correlation with Stroop parameters which is in line with previous reports ( van Koolwijk et al, 2009 ; Mutlu et al, 2018 ). Our findings suggest that GCIPL thickness and SVC density may reflect cognitive dysfunction which is in line with previous reports ( Jones-Odeh et al, 2016 ; Ko et al, 2018 ; Girbardt et al, 2021 ; Kim et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…A population-based study investigating 11,124 eyes of 6,471 subjects found that low cognitive performance was mainly associated with thinner RNFL thickness and suggested that RNFL thickness would be an indicator for cognitive performance and present the potential for prediction of future cognitive decline. 38 We found that both the right and left eye RNFL thickness and the Digit Span Test performances were moderately correlated in patients. The Digit Span Test evaluates working memory, 39 Similarly, in a follow-up study conducted in 2017, the thickness of the RNFL was associated with the test scores that evaluated episodic memory, and it was emphasized that the RNLF thickness could be a marker reflecting the cognitive deficits in geriatric population.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, studies exploring the associations between retinal layers and cognitive function in young populations are very scarce. Indeed, the previous studies that have explored these associations were mainly conducted among adults (over 40 years) (Girbardt et al, 2021; Jeevakumar et al, 2022; Khawaja et al, 2016; Ko et al, 2018; Merten et al, 2020). To our knowledge, only one previous study in this field has included young people, showing that retinal layer thickness assessed in middle age was associated with cognitive performance in childhood and adulthood (Barrett‐Young et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies exploring the associations between retinal layers and cognitive function in young populations are very scarce. Indeed, the previous studies that have explored these associations were mainly conducted among adults (over 40 years) (Girbardt et al, 2021;Jeevakumar et al, 2022;Khawaja et al, 2016;Ko et al, 2018;Merten et al, 2020).…”
Section: Discussionmentioning
confidence: 99%